2005
DOI: 10.3106/1348-6160(2005)30[s53:dotwso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the white-toothed shrews of the genus Crocidura (Insectivora: Soricidae) in East and Southeast Asia

Abstract: The genus Crocidura is one of the largest genera among mammals and widely distributed in Eurasia, Africa, and Southeast Asia. We review the recent advances in taxonomic and phylogenetic studies of this genus in East and Southeast Asia. Sympatric distributions of two or more species are known in several localities. Karyotypes of East and Southeast Asian species are divided into several groups. From karyological comparison and molecular phylogeny, those groups are suggested to have formed by geographical isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Most studies involving protein, chromosomal, and recent molecular data suggest the evolutionary division of Crocidura into Afrotropical and Asian lineages (Maddalena 1990;Maddalena & Ruedi 1994;Ruedi 1998;Bannikova et al 2006;Dubey et al 2008;Lavrenchenko et al 2009); however, the monophyly of these clades is still insufficiently supported. Yet both karyological and molecular data strongly suggest that East Asian Crocidura comprise a mixture of southern and northern faunal elements (Motokawa et al 2000(Motokawa et al , 2005Dubey et al 2008) and their relationship with Afrotropical species is very complex due to several transcontinental faunal exchanges hypothesized between Eurasia and Africa (Dubey et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies involving protein, chromosomal, and recent molecular data suggest the evolutionary division of Crocidura into Afrotropical and Asian lineages (Maddalena 1990;Maddalena & Ruedi 1994;Ruedi 1998;Bannikova et al 2006;Dubey et al 2008;Lavrenchenko et al 2009); however, the monophyly of these clades is still insufficiently supported. Yet both karyological and molecular data strongly suggest that East Asian Crocidura comprise a mixture of southern and northern faunal elements (Motokawa et al 2000(Motokawa et al , 2005Dubey et al 2008) and their relationship with Afrotropical species is very complex due to several transcontinental faunal exchanges hypothesized between Eurasia and Africa (Dubey et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Shrews (Soricomorpha: Crocidura) have proven a useful clade for testing a number of biogeographic hypotheses in East Asia, as they are ubiquitous and diverse throughout the region (e.g. Ruedi et al, 1998;Motokawa et al, 2005;). However, the taxonomy of Crocidura remains complex and somewhat unresolved, as new species and island populations continue to be discovered (Ruedi, 1995;Lunde et al, 2004;Hutterer, 2007;Jenkins et al, 2007Jenkins et al, , 2009Abramov et al, 2008) and molecular evidence has revealed several cases where taxonomy does not fully account for evolutionary history, as inferred from DNA sequence data (Ohdachi et al, 2004;Dubey et al, 2008;.…”
mentioning
confidence: 99%
“…The geographical distributions and morphological distinction of C. tanakae and C. attenuata were resolved based on a large number of specimens [10]. Compared with fewer studies in China, there are extensive studies of Crocidura in Southeast Asian countries and regions, such as in Vietnam [3,11], Malaya and Indonesia [12][13][14][15], Philippines [16,17] and Taiwan [17][18][19], Korea and Japan [20][21][22][23]. Although these previous studies did much to improve our understanding of the evolutionary relationships and taxonomy of Crocidura in Southeast Asian and regions, they rarely sampled species in China.…”
Section: Introductionmentioning
confidence: 99%